Increasing the Reading Interest of Students with Intellectual Disability through 15-minute Reading Movement and the Role of Parents during the Covid-19 Pandemic - Vania Nyepi Lianti; Asri Wibawa Sakti; Asep Rudi Irawan (JASSI ANAKKU, 2022)
The purpose of this study was to determine the increase in reading interest of students with an intellectual disability after carrying out a 15-minute reading movement and the role of parents in helping their children during the Covid-19 pandemic. The method used in this research is a case study method for two students with intellectual disabilities. The results of this study are students with intellectual disabilities become enthusiastic to read and have a high interest in reading. From these results, we get differences in the results of the pre-test and post-test. This is because students get interesting reading and support from their parents. Indeed, this movement has an impact on the reading interest of every student with intellectual disability.